Analysis Comparisonal of Financial Performance on Basic Chemical Sub Sector Manufacturing Company before and During Pandemic Covid 19 Registered Indonesia Stock Exchange Period 2019-2020 - Cahyo Pramono; Maya Macia Sari; Eka Soraya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The study was to find out the different financial performance of Manufacturing Companies in the Basic Chemical Sub Sector before and after the Covid 19 Pandemic in 2019 between 2020. Financial performance in this study uses the profitability ratio, liquidity ratio, solvency ratio, activity ratio, and market value ratios. The population in this study was 12 Manufacturing Companies in the Basic Chemical Sub Sector and the sample was 12 Manufacturing Companies in the Basic Chemical Sub Sector with two years of observation from 2019 until 2020 period. Technique collection data uses library research and indirect observation which can be accessed on the site www.idx.co.id. The analytical technique used in this study is descriptive statistics, normality test method (Kolmogorov-Smirnov), parametric test (Paired sample t-test), and nonparametric test (Wilcoxon signed test). The result of this study showed that return on equity there was no significant difference before and after Covid 19 Pandemic, debt to assets ratio has been significant difference before and after Covid 19 Pandemic, debt to equity ratio there was no significant difference before and after Covid 19 Pandemic, a working capital turnover there was no significant difference before and after Covid 19 Pandemic, total assets turnover has been significant difference before and after Covid 19 Pandemic.